AB1155 Self-Reported Rheumatic Diseases and Early Retirement in Portugal – Results from the Portuguese Epidemiology Study on Rheumatic Diseases (Epireumapt). (9th June 2015) - Laires, P.A.; Canhão, H.; Gouveia, M.; Rodrigues, A.; Gouveia, N.; Branco, J.
Abstract : Background: Chronic diseases and in particular rheumatic diseases (RD) may lead to early retirement, generating substantial costs to society. Objectives: We aim to examine the association between self-reported RD and early retirement by using large real-world observational data. Methods: EpiReumaPt was a national, cross-sectional, population-based study conducted from September 2011 to December 2013. 10, 661 inhabitants were randomly surveyed in order to capture and characterize all cases of RD within a representative sample of the Portuguese population, which were stratified by administrative territorial units (NUTSII). In this analysis we used all participants aged between 50 and 65 years old, near the official retirement age (N=2, 792; females: 1, 727). The association of self-reported RD and early retirement was tested using individual level logistic regression. All estimates were computed as weighted proportions, in order to take into account the sampling. Results: 29.9% of the Portuguese population with ages between 50 and 64 years old were officially retired. Among these, 43.2% were retired due to ill-health, which in turn about a third (30.4%) was specifically due to RD. Thus, 13.1% of all retirees self-reported RD as the main reason for early retirement. More than a third (34.2%; females: 46.3%) of all study population self-reported RD, being also more likely to self-report other main chronic disease (OR: 3.4; CI: 2.53-4.65; p <0.001). 35.2% of RD respondents were retired versus 27.2% of those non-RD ( p =0.025). Prevalence of self-reported RD seems to be associated with early retirement (unadjusted OR: 1.45; CI: 1.05-2.01; p =0.025). Some other characteristics are also associated with early retirement, in particular older age, male gender and presence of other chronic diseases. RD association tends to be independently associated with early retirement (adjusted OR: 1.41; CI: 1.03-1.95; p =0.031). Conclusions: These results are in line with previous data from the National Health Survey conducted in Portugal nearly a decade ago and confirms the impact that self-reported RD still have on early retirement. Nevertheless, further analysis should be done in order to analyze clinically confirmed RD and to address the different RD and its relationship with early retirement. Disclosure of Interest: None declared